Training needs assessment of farm women in dairying practices - KUMAR, SANJEEV; SHARMA, RAJ KISHORE; SINHA, RAVI RANJAN KUMAR; KUMAR, SURYAMANI; RANJAN, SANJEEV (The Indian Journal of Animal Sciences, 2021)
A study was conducted in Nalanda district of Bihar, to assess the training needs of farm women engaged in dairying. It was observed that out of the five major dairy farm operation studied, the dairy farm women needed foremost training in health care and disease control. Under the minor operations most preferred knowledge needed were proper design of cattle shed, selection of breeds, compounding balanced feed preferably using locally available ingredients, vaccination, and banking and insurance. The dairy farm women expressed their willingness to have their training in the summer season, preferably in the month of March at their resident village. Majority of respondent (67%) were expecting the duration of training as one week and 65% farm women opined to have training with an interval of one year.